Exact optical solitons of Radhakrishnan-Kundu-Lakshmanan equation with Kerr law nonlinearity - Ghanbari, Behzad; İnç, Mustafa; Yusur, Abdullahi; Bayram, Mustafa (World Scientific Publ Co Pte Ltd, 2019)
A new generalized exponential rational function method (GERFM) is used to acquire some new optical solitons of Radhakrishnan-Kundu-Lakshmanan (RKL) equation with Kerr nonlinearity. This equation is used to model propagation of solitons through an optical fiber. The well-known exponential rational function method is also a special case of the GERFM. The results reveal that the mentioned method is efficient and simple for solving different nonlinear partial differential equations.
Keywords: Optical solitons; RKL; GERFM; traveling wave solutions